Tools for Developing, Implementing, and Evaluating State Policy - Melanie Besculides, DrPH; Bernadette Ford Lattimore, MPH; So O'Neil, MS (Centers for Disease Control and Prevention, 2008)
Policy can improve health by initiating changes in physical, economic, and social environments. In contrast to interventions focused on individual people, policies have the potential to affect health across populations. For this reason, the Division for Heart Disease and Stroke Prevention of the Centers for Disease Control and Prevention (CDC) advises states funded under the Heart Disease and Stroke Prevention Program to engage in activities supporting the development and maintenance of policies that can help reduce the burden of cardiovascular disease.Currently, the Division for Heart Disease and Stroke Prevention funds programs in 33 states and the District of Columbia to promote cardiovascular health. One goal of these programs is to build states' capacity to develop, implement, track, and sustain population-based interventions that address heart disease and stroke. Because of the critical role of policy in these activities, CDC provides guidance in developing, implementing, and evaluating policy. In 2004, the division contracted with Mathematica Policy Research, Inc, to conduct the Heart Disease and Stroke Prevention Policy Project, which included development of an online database of state heart disease and stroke prevention policies and a mapping application to show which states have these policies.We discuss the method for developing the database, mapping application, and other tools to assist states in developing, implementing, and evaluating heart disease and stroke prevention policies. We also highlight lessons learned in developing these tools and ways that states can use the tools in their policy and program planning.